(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article aims to investigate the role and impact of borrowed complex words in educational contexts, focusing on their effects on teaching practices and student comprehension. Utilizing a mixed-methods approach, we analyzed educational texts, conducted surveys with educators, and performed reading comprehension tests with students across different grade levels. The analysis revealed that borrowed complex words, predominantly from Latin and Greek, are prevalent in academic materials and can enhance linguistic precision. However, they also introduce significant cognitive challenges, especially for students with diverse linguistic backgrounds. The conclusion emphasizes the necessity for educators to adopt balanced instructional strategies that incorporate borrowed words effectively while promoting understanding and accessibility, thereby supporting equitable educational outcomes for all learners.